Legislatif Perempuan di Dataran Tinggi Gayo: Peluang dan Tantangan - Sutrisno Sutrisno; Ali Mustafa (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2017)
This paper aims to explore opportunities and challenges of women becoming legislative members in the 2014-2019 election in the Gayo highlands covering Central Aceh, Bener Meriah, and Gayo Lues. Our research find is the political dynasty became main factor cause opportunities of women's election as members of the legislature in the three regions. Even political figures, party cadres and NGO activists who are generally another major factor supporting women's electoral opportunities in electoral politics are not a factor supporting women's election to legislative members in the Gayo highlands. This phenomenon indicates that the quality and quantity of women representation in DPRK Aceh Tengah, Bener Meriah, and Gayo Lues were decreased, besides the strengthening of the paradigm of a society that still highly uphold the culture of patriarchy within the Islamic Shari'ah region of Aceh. Qualitative research methods are used in assessing the opportunities and challenges of women's political election to obtain in-depth data through in-depth observation and interviews as well as library studies in support of the general picture through related references. The phenomenon of women's election in the legislature concludes that the strengthening of patriarchal culture through the edict law that regulates the taboo (sumang) merges with the understanding of women and Islamic sharia which is the main challenge that causes women's election to become legislative members.